2010
DOI: 10.1158/1078-0432.ccr-09-0379
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Clinical Trial of Ixabepilone (Ixempra; BMS-247550; NSC 710428), an Epothilone B Analog, in Patients with Metastatic Renal Cell Carcinoma

Abstract: Purpose: Ixabepilone (Ixempra; BMS-247550) is an epothilone B analog and nontaxane microtubulestabilizing compound with clinical activity in a range of solid tumors. This phase II study was conducted to assess the efficacy and safety of ixabepilone in patients with metastatic renal cell carcinoma.Experimental Design: Patients with metastatic renal cell carcinoma who had measurable disease and had not received previous cytotoxic or targeted therapy were treated with 6 mg/m 2 ixabepilone i.v. daily for 5 days ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Since calculations of g and d use the time elapsed between assessments, comparisons amongst studies can be made regardless of differences in assessment protocols. The right panel of Figure 3 depicts dot plots of log g values derived in our previous studies in patients with mRCC, treated with a placebo, bevacizumab or ixabepilone 9,11,15,16 as well as the present four data sets (sunitinib or IFN-α, each measured by study investigators or central review ). Confirming the waterfall plots, g values for sunitinib-treated patients are significantly slower at p<0.0001 [ investigators / central review log g values were: sunitinib=−3.09/−2.94; IFN-α=−2.81/−2.78].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since calculations of g and d use the time elapsed between assessments, comparisons amongst studies can be made regardless of differences in assessment protocols. The right panel of Figure 3 depicts dot plots of log g values derived in our previous studies in patients with mRCC, treated with a placebo, bevacizumab or ixabepilone 9,11,15,16 as well as the present four data sets (sunitinib or IFN-α, each measured by study investigators or central review ). Confirming the waterfall plots, g values for sunitinib-treated patients are significantly slower at p<0.0001 [ investigators / central review log g values were: sunitinib=−3.09/−2.94; IFN-α=−2.81/−2.78].…”
Section: Resultsmentioning
confidence: 99%
“…The horizontal lines in each set are the median values and the 25% and 75% limits. The growth rate constants are shown from left to right for patients with RCC enrolled on the NCI placebo vs. bevacizumab study 15 , the NCI ixabepilone study 16 , and the two arms of the sunitinib Phase III study 3, 13 . Using data from study investigators , the median g was 0.0015 per days and median log g was −2.81 (25% to 75%: −2.38 to −3.54) for IFN-α-treated patients compared with a median g of 0.00082 per days and median log g of −3.09 (25% to 75%: −2.70 to −3.46) for the sunitinib-treated cohort, significantly different at p<0.0001.…”
Section: Figurementioning
confidence: 99%
“…Finally, the most recent phase II study conducted with monochemotherapy was published in 2010 by Huang et al [28]; it included a large sample of patients and explored the activity of ixabepilone, a novel microtubuletargeting agent analog to epothilone B, in patients affected by mRCC. The study reported the good tolerability profile of ixabepilone, with low toxicity; the results in terms of RR were more encouraging than those of the trials presented above, with an objective RR of 12.6%, including PR and CR.…”
Section: Review Monochemotherapymentioning
confidence: 99%
“…Up to now, more than six epothilones or their derivatives are being evaluated in different stages of clinical trials, and ixabepilone has been approved for the clinical treatment of advanced breast cancer by the Food and Drug Administration of the USA (Brogdon et al 2014; Huang et al 2010; Rivera et al 2008; Roche et al 2007). Epothilones are originally produced by the myxobacterium Sorangium cellulosum (Gerth et al 1996), which has a long doubling time and limited molecular performance tools.…”
Section: Introductionmentioning
confidence: 99%